STEREOSELECTIVE SYNTHESIS OF AN ISOQUINOLINOPYRROLIDINONE BY ACYLIMINIUM ION CYCLIZATION OF CHIRAL HYDROXYLACTAMS - LEE, YS; KANG, DW; LEE, SJ; PARK, H (MARCEL DEKKER INC, 1995)
Studies on the stereoselective synthesis of a pyrrolidinoisoquinoline derivative using acyliminium ion cyclization of hydroxylactams are described. Cyclization reaction of chiral hydroxylactams 2a similar to c, derived from (L)-tartaric acid and phenethylamine, afforded one diastereomer 3 under a variety of acidic conditions in moderate to good yields.